Team adaptive capacity and adaptation in dynamic environments: A scoping review of the literature - Natalie Sanford; Olivia Lounsbury; Gabriel Reedy; Dame Anne Marie Rafferty; Janet E. Anderson (Human Factors in Healthcare)
Healthcare systems rely on the expertise, ingenuity, and resilience of healthcare teams to maintain safe and high-quality care in complex, variable, and resource-constrained environments. Research has suggested that successful team adaptation prevents patient harm, optimises efficiency, and keeps healthcare systems running. Team adaptation is a central concept in both teamworking and organisational resilience theory, but team adaptation and its associated concepts, specifically team adaptive capacity, remain underspecified, ill-defined, and poorly understood in healthcare. Other high-risk industries, such as aviation, military, and nuclear power, may have a more extensive evidence base that can inform conceptualisations in healthcare and beyond. This scoping review synthesizes the cross-disciplinary literature on team adaptation, proposes a new definition for team adaptive capacity, and develops a model for understanding team adaptation, its outcomes, and antecedents: the team adaptive cycle.